Multiple sclerosis masquerading as Alzheimer-type dementia: Clinical, radiological and pathological findings. (April 2016) - Tobin, WO; Popescu, BF; Lowe, V; Pirko, I; Parisi, JE; Kantarci, K; Fields, JA; Bruns, MB; Boeve, BF; Lucchinetti, CF
Background and objectives: We report a comprehensive clinical, radiological, neuropsychometric and pathological evaluation of a woman with a clinical diagnosis of AD dementia (ADem), but whose autopsy demonstrated widespread demyelination, without Alzheimer disease (AD) pathology. Methods and results: Initial neuropsychometric evaluation suggested amnestic mild cognitive impairment (aMCI). Serial magnetic resonance images (MRI) images demonstrated the rate of increase in her ventricular volume was comparable to that of 46 subjects with aMCI who progressed to ADem, without accumulating white matter disease. Myelin immunohistochemistry at autopsy demonstrated extensive cortical subpial demyelination. Subpial lesions involved the upper cortical layers, and often extended through the entire width of the cortex. Conclusions: Multiple sclerosis (MS) can cause severe cortical dysfunction and mimic ADem. Cortical demyelination is not well detected by standard imaging modalities and may not be detected on autopsy without myelin immunohistochemistry.